Evaluation of the Military Spouse Employment Partnership : progress report on first stage of analysis - Gonzalez, Gabriella (Research report (Rand Corporation) ;, 2015)
"The frequent relocations associated with military service place distinct demands on service members and their families and can complicate military spouses' career trajectories. Recognizing this challenge, the White House published a directive in 2011 ordering the Department of Defense to expand the Army Spouse Employment Partnership, which had recruited 52 employer partners since its inception in 2003 to assist military spouses seeking employment, to serve Navy, Marine Corps, and Air Force spouses. The resulting Military Spouse Employment Partnership, launched on June 29, 2011, is one of four initiatives under the Department of Defense's Spouse Education and Career Opportunities program. In December 2014, the U.S. Congress mandated an evaluation of the Partnership and the Office of the Deputy Assistant Secretary of Defense for Military Community and Family Policy sponsored RAND to assess the extent to which the Partnership addresses its objectives. This report documents the first phase of research to help meet the congressional requirement for a 'report evaluating the progress of military spouse employment programs.' This research should be of interest to policymakers responsible for programs or oversight of programs supporting military spouse quality of life, as well as scholars who study military spouse issues and program evaluation"--Publisher's web site